Rethinking Development Finance - Kim, Jim Yong (World Bank, Washington, DC, 2019)
Jim Yong Kim, President of the World Bank Group, spoke about the forces in the world that are making us fundamentally rethink the approach to development at the World Bank Group. He described three paths. The first path is to accelerate inclusive and sustainable economic growth, by laying the foundations for more effective public services, by improving governance and tackling corruption, by accelerating infrastructure investment, by lowering real and perceived risks for private investment, by making trade work for everyone, and by creating markets to bring the benefits of private sector rigor and innovation to developing countries. The second path is to invest more, and more effectively in people; the premium on human capital will get higher and higher every year. The demands for digital competency are accelerating. Investing in human development must start early – by ensuring that pregnant women have access to prenatal healthcare, including the right nutrition; by preventing malnutrition in children, so they can develop properly; by ensuring access to quality health care for all; by providing education that prepares students for the jobs of the future; and by building social safety nets that meaningfully protect the poor. The third path is to foster resilience to global shocks and threats. We’re living in a time of multiple overlapping crises: pandemics, climate change, refugees, famine. It is critically important to help countries prepare for these crises.